Experimental and Numerical Investigation of Cyclic Grouting Compactness in Prestressed Tendon Ducts - Chulong Chen; Zeliang Yang; Shunxin Yu; Jinzhou Chen (Advances in Civil Engineering)
The grouting parameters for cyclic grouting are often set based on pressure grouting or experience, which makes it difficult to achieve optimal compactness. To better comprehend the distribution of the cement slurry and improve grouting compactness, the flow mechanism was analyzed to determine the key grouting parameters. Subsequently, a cyclic grouting experiment was conducted, and the grouting compactness was detected using the impact-echo method. For further study, a 2D numerical model was established, and the influence of grouting parameters on compactness was investigated. The results revealed that grouting compactness was influenced by the duct length, slurry viscosity, and grouting pressure. However, based on the technical specifications, the impact of slurry viscosity on compactness was found to be minimal. Longer ducts posed a greater challenge to achieving dense grouting and required higher grouting pressures. Nevertheless, when the duct length exceeded 330 m, attaining dense grouting became increasingly difficult. Finally, grouting pressures were recommended for ducts of varying lengths by considering both grouting compactness and cost. The results of this study offer guidance for the practical applications of cyclic grouting in engineering.